3D visualisation of voids in grapevine flowers and berries using X‐ray micro computed tomography. (6th January 2021) - Xiao, Z.; Stait‐Gardner, T.; Willis, S.A.; Price, W.S.; Moroni, F.J.; Pagay, V.; Tyerman, S.D.; Schmidtke, L.M.; Rogiers, S.Y.
Abstract: Background and Aim: X‐ray micro computed tomography (micro‐CT) is a non‐destructive 3D imaging technique that has been applied to plant morphology and anatomical studies to gain a better understanding of physiological phenomena in vivo. It is particularly useful for imaging voids in undisturbed fragile tissues and therefore may be applied to the delicate flowers and soft berries of Vitis vinifera . The characterisation of gas spaces and channels can offer insights into the process of tissue aeration and this may have implications on cell function and vitality. We assessed the use of micro‐CT to visualise voids within these reproductive organs. Methods and Results: The internal structures of flowers and berries were captured through rapid micro‐CT scanning and subsequently were recreated in 3D using image processing. The relative positions of the developing flower parts encased within the flower cap were visualised. Low density/porous tissue was identified within the pedicel and receptacle, connecting the lenticels with the interior of the berry. Voids were present in the proximal mesocarp of mature berries forming a 'detachment zone' in both seeded and seedless cultivars. Voids permeated the mesocarp of mature seedless grape cultivars, but not seeded grapes. Conclusion: Micro‐CT offers new insights regarding the distribution of voids on the morphology and compositional heterogeneity of organs that are difficult to dissect and/or view with light microscopy. Significance of the Study: A better understanding of the physiology and functionality of grapevine reproductive tissues may be achieved by 3D visualisation of internal structure in vivo.